Safety and efficacy of traditional Chinese medicine, Qiaoshao formula, combined with dapoxetine in the treatment of premature ejaculation: An open‐label, real‐life, retrospective multicentre study in Chinese men. (24th November 2020) - Guo, Jun; Wang, Fu; Zhou, Qing; Geng, Qiang; Gao, Qinghe; Zhang, Rui; Zhang, Chunhe; Xuan, Zhihua; Cai, Jian; Bin, Bin; Han, Qiang; Guo, Boda; et al.
Abstract: To evaluate the safety and efficacy of Chinese medicine, Qiaoshao formula combined with dapoxetine was used for the treatment of premature ejaculation in a real‐life setting. Nine hundred and five males diagnosed with premature ejaculation were reviewed in this retrospective cohort study. We divided the patients into two groups: dapoxetine alone and Qiaoshao formula combined with dapoxetine according to actual interventions provided to patients in clinics. The perceived intravaginal ejaculation latency time and the premature ejaculation profile measures markedly improved in both groups. However, in men with severe premature ejaculation (baseline perceived intravaginal ejaculation latency time <1 min) and those with baseline age ≤30 years, the perceived intravaginal ejaculation latency time was slightly but significantly longer with combined therapy than with dapoxetine alone ( p < .05). Therefore, combined therapy involving the Qiaoshao formula and dapoxetine proved to safe as well as effective for treating premature ejaculation while prolonging the perceived intravaginal ejaculation latency time, which significantly improved the overall satisfaction of the patient and likely that of the couple.